Analisis Kepemimpinan Para Pemimpin Organisasi Kemahasiswaan di Universitas Negeri Medan - Hapni Laila Siregar; Farhan Farhan; Irvan Affandi; Isna Firdasari Ajwa; Riris Amigo Simatupang; Rizky Ramadhan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In the context of the development of Student organizations, leadership plays an important role in determining the direction, quality, and success of an organization. Leadership is defined as something that influences others in order to realize the goals of the "organization Sakdiah" states, that leadership is a person's ability to lead and occupy positions, as leaders of work units, so that with his positive behavior he contributes to the achievement of the organization. This study examines the implementation of leadership spirit in the context of organizational learning at the Faculty of Economics, Medan State University. This study used qualitative research methods with 35 students as participants. Data is collected through online surveys using Google Forms. The analysis is based on five indicators: honest, responsible, problem-solving ability, trustworthy, and sensitive to input. The results showed that 53.32% of students rated the leadership of faculty at the university as good, although it needs improvement. The study shows that to improve leadership, organizational leaders must focus on self-development, learn from experience, and focus on organizational improvement.